Interdisciplinary perspectives on sustainable development achieving the SDGs through education, wellbeing, and innovation : [proceeding of the International Sustainability Conference, August 21-22, 2022] - Karras, Dimitrios A.; Oruganti, Sai Kiran; Ray, Sudeshna (CRC Press, 2024)
1. Power and Discourse in La Fontaine's Beast Fables 2. Lockdown: Real-life Paradoxical Experience to Sustain Human Relationships, Healthy Lives, and Well Being 3. Effect of Parenting Stress on Parenting Sense of Competence AmongMothers of Children with ADHD 4. Sustainable Development Goals and Juvenile Justice System: A Comparative Analysis5. Influence of Karma at Workplace: With Special Reference to Higher Education Institutions in South Gujarat Region6. Cross-Walk of Professional Competencies for Social and Emotional Wellbeing to Cater Mental Health Problems in Schools 7. Emotional Intelligence Manages Sustainable Development for an Organization -the Contribution of Psychological Well-Being 8. The Enactment of Social Sustainable Goals in IT Organizations 9. Role of Higher Education in Achieving the Sustainble Development Goals (SDGs) 10.
Keywords: Sustainable development / Congresses; TECHNOLOGY / General; TECHNOLOGY / Environmental Engineering & Technology; BUSINESS & ECONOMICS / Development / Sustainable Development; Konferenzschrift